Effects of maize residue removal on soil quality and greenhouse gas emissions in Iowa - Al-Kaisi, Mahdi; Guzman, Jose (Agrociencia Uruguay, 2012)
Maize residue is an important component of soil carbon (C) budget and development of soil quality indices. However, maize residue in recent years has been considered as another potential feedstock source for ethanol production in addition to or alternative to maize grain. The current emphasis on using maize residue as a feedstock for future ethanol production presents a soil and environmental challenge that needs to be addressed. Additionally, there have been few studies that examine greenhouse gas (GHG) emissions from agriculture soils under different residue removal rates, various N rates, and tillage practices and their interactions effects on soil C dynamics and GHG emissions. The objective of this study was to examine potential changes in soil C sequestration and GHG emissions under no-tillage (NT) and conventional tillage (CT) and nitrogen fertilization rates of 0, 170, and 280 kg N ha-1 with variable rates of residue removal (0, 50, and 100%). Field studies were established in fall of 2008 on two sites, a poorly-drained soil at the Iowa State University Agronomy Research Farm (North central, IA) and a well-drained soil at the Armstrong Research and Demonstration Farm (Southwest, IA) in continuous maize. After two years of residue removal, soil C, water inﬁ ltrations, aggregate stability and bulk density was measured. After every harvest, crop measurements included maize grain yield, above-ground biomass, and root-biomass. Weekly measurements of soil surface CO2, and N2O emissions coupled with soil moisture and temperatures were collected. Additionally, C budgets were calculated for different treatments. These measurements provide insights on whether these management practices resulted in net gains or losses of C sequestration and atmospheric CO2. Findings suggest that sites for this study were a signiﬁcant net sink for atmospheric CO2-C, even when maize residue was removed and under different tillage and N fertilization (when applied) management. Applications of N had the largest effect on N2O-N emissions, where greater N2O-N emission was associated with high N rates. In addition, signiﬁcant declines in soil quality properties were observed after only two years of residue removal. The severity of soil quality deterioration due to residue removal varied with different tillage and N managements.